ARCHITECTURE OF THE THIRD REICH IN POLAND: A CONTESTED HERITAGE? (City: History, Culture, Society, 2026)
The article analyses architectural heritage of the Third Reich in Poland as an example of dissonant heritage shaped by the traumatic experience of the twentieth century. It examines the evolution of approaches to cultural heritage—from the cult of monuments to the “duty of memory,” which underpins contemporary cultures of collective remembrance. Particular attention is given to the Polish context, where the Holocaust, shifting state borders, ethnic cleansing, and totalitarian ideologies have produced profound conflicts of memory and nonmemory.Architectural heritage of the Third Reich in Poland is conceptualized as a “heritage of atrocity,” closely connected to Nazi policies of occupation, genocide, and urban restructuring. At the same time, the article emphasizes the necessity of scholarly analysis within art history and heritage studies, as some realized projects have become an integral part of the contemporary landscape. Eventually, it highlights the limitations of purely inventory-based approaches and argues for interpreting this heritage as a socially and politically sensitive phenomenon.
Keywords: dissonant heritage; architecture of the Third Reich; heritage; culture of memory; memory politics; Poland